Financial frictions: Micro vs macro volatility - Seungcheol Lee; Ralph Luetticke; Morten O. Ravn (European Central Bank (ECB), 2021)
We introduce frictional financial intermediation into a HANK model. Households are subject to idiosyncratic and aggregate risk and smooth consumption through savings and consumer loans intermediated by banks. The banking friction introduces an endogenous countercyclical spread between the interest rate on savings and on loans. This interacts with incomplete markets because borrowers and savers face different intertemporal prices, and induces a time-varying mass point of high MPC households. Aggregate shocks through their impact on the spread give rise to consumption inequality. We show this mechanism to be empirically relevant. Ex-ante macro prudential regulation reduces welfare by reducing consumption smoothing.
Keywords: C11; D31; E32; E63; 330; Business cycles; financial frictions; incomplete markets; macroprudential regulation; monetary policy